Effectivity and renal safety of cyclosporine and methylprednisolone combination therapy in patients with systemic lupus erythematosus (sle) - Wuryana, Desantika; Suryana, Bagus PP; Yulistiani, Yulistiani (Folia Medica Indonesiana, 2016)
Cyclosporine and methylprednisolone combination are second line therapy for moderate to severe systemic lupus erythemathosus. Some study suggest that the combination were effective to decrease of systemic lupus erythematosus disease activity. But record from the study, cyclosporine cause nephrotoxicity side effect. Therefore, this study should be considered to monitore therapy effect on disease activity and renal side effect. The aim of this study is to analyze the effect of cyclosporine and methylprednisolone combination therapy on disease activity in systemic lupus erythematosus (SLE) assessed by MEX-SLEDAI and renal side effect assessed by creatinine, ureum and proteinuria. A cohort, observational prospective study was conducted to determine the effect of cyclosporine and methylprednisolone combination therapy on disease activity of SLE and renal side effect of this combination. Patients who met criteria were given cyclosporine and methylprednisolone combination that normally renal function tests. MEX-SLEDAI score, creatinine, ureum and proteinuria were measured for fourth times (one time in one mounth), before study, 1st mounth, 2nd mounth, and 3rd mounth. The study comprised 9 patients SLE were given cyclosporine and methylprednisolone combination that normally renal function tests. All patients were female and had productive age. At 3rd mounth, there was increase patients who had MEX-SLEDAI score <2 (55,6%) and one patient (11,1%) had increase of creatinine, ureum and proteinuria. In conclusion, cyclosporine and methylprednisolone combination therapy showed the effectiveness and safety in 88,9% patients and renal dysfunction in 11,1% patients.